Quality of Life of the Population: the Impact of Digitalization - Barlybaev Adigam; Ishnazarova Zulfiya; Sitnova Inna (E3S Web of Conferences, 2021)
The article analyzes the impact of digitalization on the life population quality, identifies areas, identifies the positive and negative impact of digitalization on the qualitative characteristics of the population’s life. The life quality is one of the important indicators of the level of development of society; it is a complex systemic integral characteristic of satisfaction with material and non-material factors of life of the population living in a certain territory. Since the environment and environmental conditions are constantly changing, various trends and patterns occur, the trends and requirements of our time, inevitably affect the life quality. One of such conditions, gaining momentum at the present time, is digitalization. Digitalization is the introduction of modern digital technologies in various spheres of life and production. Currently, in all types and levels of economic processes in the world and in individual countries, the so-called “digitalization” is gaining momentum - the active use of information and communication technologies. There is a need to accept digitalization as a universal process, adapt to it and use its levers for the best possible result for society. In nine areas, digitalization directly affects the life quality - the city, education, healthcare, economy, finance, information systems, infrastructure, business, and agriculture.